ANALISIS STRUKTUR IKLAN WARUNG BU KRIS - Agus Darma Yoga Pratama; Ni Komang Purwaningsih (Kulturistik: Jurnal Ilmu Bahasa dan Budaya, 2021)
This research investigated advertising structure, strategy, and also the impact of advertising promotion on purchasing decisions of Warung Bu Kris’s food. The data in this study were collected through the observation method, namely by observing the use of words, phrases, sentences, icons, and images in food product advertisements and grouping them. The researcher used screenshots as a documentation technique in collecting the data and then categorizing them into groups. The data was analyzed based on the problems raised. The intralingual method used in this research. The finding showed that the structure in the food advertisement of Warung Bu Kris was headline-illustrations-body copy-signature line-standing details and headline-body copy-standing line. The advertising structure reflected the marketing strategy used by Warung Bu Kris’ owner, including establishing credentials, pressure tactics, and also offering incentives. The advertisements on Instagram influenced customer demand for food in terms of attitude towards the ad and click through rates. Keywords: advertisement; food; promotion; structure